PROBLEM-SEARCH ACTIVITIES IN THE LESSON AS A MEANS OF STUDENT DEVELOPMENT (Pedagogy of Higher and Secondary Education, 2022)
In article, the author investigates features of thought process, the law of development of cognitive activity, characterizes stages of informative search, proves a role of the teacher at creation of a problem situation and analyzes conditions of incision of pupils n problem search activity.
Keywords: thought process; informative search; problem training; a probem sinaton; independen activity